Discontinuation of biologic DMARDs in a real-world population of patients with rheumatoid arthritis in remission: outcome and risk factors. (12th April 2021) - Arnold, Simone; Jaeger, Veronika K; Scherer, Almut; Ciurea, Adrian; Walker, Ulrich A; Kyburz, Diego
Abstract: Objectives: Data from randomized controlled trials have shown the feasibility of discontinuation of bDMARD therapy in patients with RA that have reached remission. Criteria for selecting patients that are likely to remain in remission are still incompletely defined. We aimed to identify predictors of successful discontinuation of bDMARD therapy in the Swiss Clinical Quality Management (SCQM) registry, a real-world cohort of RA patients. Methods: RA patients in DAS28-ESR remission who stopped bDMARD/tsDMARD treatment were included. Loss of remission was defined as a DAS28-ESR > 2.6 or restart of a bDMARD/tsDMARD. Time to loss of remission was the main outcome. Kaplan–Meier methods were applied and Cox regression was used for multivariable analyses adjusting for confounding factors. Missing data were imputed using multiple imputation. Results: A total of 318 patients in a bDMARD/tsDMARD-free remission were followed between 1997 and 2017. In total, 241 patients (76%) lost remission after a median time of 0.9 years (95% CI: 0.7, 1.0). The time to loss of remission was shorter in women, in patients with a longer disease duration >4yrs and in patients who did not meet clinical disease activity index (CDAI) remission criteria at baseline. Remission was longer in patients with csDMARD therapy during b/tsDMARD free remission [hazard ratio (HR) 0.8, P =0.05, 95% CI: 0.6, 1.0]. Conclusion: In a real-world patient population, the majority of patients who discontinued b/tsDMARD treatment lost remission within <1 year. Our study confirms that fulfilment of more rigorous remission criteria and csDMARD treatment increases the chance of maintaining b/tsDMARD-free remission.